1993
DOI: 10.1210/jcem.76.1.8421076
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine stimulation of interleukin-1 in the growth of human thyroid carcinoma cell line NIM 1.

Abstract: We reported first in this study that human thyroid cell line NIM 1 established from a patient with papillary adenocarcinoma of the thyroid associated with hypercalcemia and peripheral neutrocytosis produced interleukin (IL)-1 alpha and IL-1 beta in the culture supernatant and cell lysate as detected by murine thymocyte proliferative response and enzyme-linked immunosorbent assay. Production of IL-1 alpha and IL-1 beta was further confirmed by the demonstration of IL-1 alpha and IL-1 beta messenger ribonucleic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The human thyroid carcinoma cell lines studied were: TPC-1 (Tanaka et al, 1987), WRO (Pang et al, 1989), NPA (Estour et al, 1989), ARO (Pang et al, 1989), FRO (Fagin et al, 1993), NIM 1 (Zeki et al, 1991) and B-CPAP (Fabien et al, 1994). They were grown in Dulbecco's modi®ed Eagle's medium (DMEM) containing 10% fetal bovine serum.…”
Section: Cell Culture and Assay Of The Transformed Statementioning
confidence: 99%
“…The human thyroid carcinoma cell lines studied were: TPC-1 (Tanaka et al, 1987), WRO (Pang et al, 1989), NPA (Estour et al, 1989), ARO (Pang et al, 1989), FRO (Fagin et al, 1993), NIM 1 (Zeki et al, 1991) and B-CPAP (Fabien et al, 1994). They were grown in Dulbecco's modi®ed Eagle's medium (DMEM) containing 10% fetal bovine serum.…”
Section: Cell Culture and Assay Of The Transformed Statementioning
confidence: 99%
“…It has recently been reported that IL-1α is produced in many human cancer cell lines, including those of bladder cancer [3], thyroid carcinoma [4,5], gastric carcinoma [6], ovarian cancer [7], squamous cell carcinoma [8][9][10], and pancreatic carcinoma [11]. We have revealed that patients with tumors stained with IL-1 antibody by immunohistochemistry showed a higher incidence of liver metastasis of gastric cancers [12].…”
mentioning
confidence: 77%
“…We have revealed that patients with tumors stained with IL-1 antibody by immunohistochemistry showed a higher incidence of liver metastasis of gastric cancers [12]. IL-1α produced by tumor cells stimulates the proliferation or the growth of thyroid cancer [4,5], gastric cancer [6], ovarian cancer [7], and colon cancer cell lines [13], and is considered to act as a promoter of invasion or metastasis via the expression of E-selectin on vascular endothelial cells [14] or via the production of matrix metalloproteinase from the tumor cells [15]. However, it has also been reported that IL-1α inhibited the growth of cell lines in thyroid cancer [16], breast cancer [17,18], and colon cancer [19].…”
mentioning
confidence: 99%
“…Diverse effects by IL-1 on the growth of cells from solid tumors have been reported. The cytokine can exert growth-inhibitory activity in some tumor cells (Bertoglio et al, 1987;Danforth and Sgagias, 1993;Gaffney and Tsai, 1986;Kilian et al, 1991;Lachman et al, 1986;Onozaki et al, 1985) but also stimulates growth of several tumor cell lines (Hamburger et al, 1987;Ito et al, 1993;Lahm et al, 1992), including autocrine growth stimulation (Zeki et al, 1993). Although these observations remain contradictory, several clinical studies with IL-1 in cancer patients are under way (Crown et al, 1991;Redman et al, 1994;Schuchter et al, 1994;Triozzi et al, 1995).…”
mentioning
confidence: 99%